Observation of manganese crusts recovered during the CHAIN 44 cruise in October 1964 in the Atlantic Ocean - T H van Andel; V T Bowen; P L Sachs; R Siever (PANGAEA, 1965)
In October 1964, a detailed geophysical and sampling survey was made of the central part of the Mid-Atlantic Ridge between 22° and 23° north latitude. The results indicate a large difference in age between the relief of the crest and that of the flanks of the Ridge and suggest that the crest portion is very young. Detailed surveys of two sediment-filled valleys on the upper western flank of the Ridge reveal different sedimentary sequences in the two valleys and indicate the probable existence of a locally controlled depositional regime and a significant local supply of sediment.
Supplement to: van Andel, TH et al. (1965): Morphology and Sediments of a Portion of the Mid-Atlantic Ridge. Science, 148(3674), 1214-1216, https://doi.org/10.1126/science.148.3674.1214